Penggunaan Alat Peraga Edukatif Dalam Kegiatan Literasi Numerasi - Umayah; Vika Putri Zamanina; Triana Putri; Diana Ayu; Fatkhurrohman (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2024)
Educational props are anything that can be used as a means or equipment for play that contains educational (educational) values and can develop all children's abilities. Numeracy literacy is the ability to use number concepts and calculation operation skills in everyday life so that numeracy literacy skills need to be introduced from an early age to be applied in everyday life. The method used is a qualitative approach with direct interview techniques to obtain data and information. The aim of this research is to determine the use of educational teaching aids in numeracy literacy learning. The results of the research show the success of learning numeracy literacy through educational teaching aids namely that students are able to name and write the number symbols 1-10 through the APE Number Tree.